Interleukin-6 trans-signaling and pathological low back pain in patients with Paget disease of bone. Issue 8 (August 2018) - Rendina, Domenico; De Filippo, Gianpaolo; Postiglione, Loredana; Covelli, Bianca; Ricciardone, Margherita; Guillaume, Séverine; Di Spigna, Gaetano; Selleri, Carmine; Merlotti, Daniela; Bianciardi, Simone; Materozzi, Maria; Muscariello, Riccardo; et al.
Abstract : Abstract: The interleukin (IL)-6 biological system plays a key role in the pathogenesis of Paget disease (PD) of bone and pathological bone pain. Bone pain, particularly in the lower back region, is the most frequent symptom in patients with PD. This case–control study aimed to evaluate the relationship between the IL-6 system and low back pain (LBP) in patients with PD. We evaluated 85 patients with PD, with the disease localized in the lumbar spine, pelvis, and/or sacrum, and classified them based on the presence or absence of LBP, before and after aminobisphosphonate treatment. We also examined 32 healthy controls without LBP. Before treatment, IL-6 levels in patients with PD were higher than those in the controls, without difference between patients with or without LBP. Patients with PD with LBP (35/85) showed higher IL-6-soluble receptor (sIL-6R) and lower soluble glycoprotein (sgp) 130 levels compared with both patients with PD without LBP and controls (sIL-6R: 46.9 ± 7.4 vs 35.4 ± 8.6 vs 29.9 ± 4.2 ng/mL; sgp130: 307.2 ± 35.4 vs 341.4 ± 41.4 vs 417.1 ± 58.5 ng/mL, respectively). Paget disease remission, 6 months after treatment, is associated with LBP improvement. This phenomenon is associated with reduced sIL-6R levels and increased sgp130 levels in patients with PD with LBP at the baseline. Considering the biological properties of IL-6, sIL-6R, and sgp130, the results of the study suggest that the perception of LBP in patients with PD could be linked to an enhanced transmission of IL-6 signal in the specialized neural system activated by nociceptors. Abstract : Interleukin-6 trans-signaling could play a key role in the pathogenesis of both Paget disease of bone and pathological low back pain in patients with Paget disease.